PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BAHASA INDONESIA BERNILAI PENDIDIKAN KARAKTER UNTUK SISWA KELAS V SD - Hasnul Fikri; Ade Sri Madona (Puitika, 2017)
This article is aimed to describe the results of validation test and limited trials of interactive multimedia-based learning media in Indonesia language teaching wich is value of character education for grade V elementary school students in order to support the implementation of Curriculum 2013. This research is a research and development research with 4-D model. The data are sourced from three validators, namely the lecturer in Indonesian language education, information technology and communication, and character building, five students and one teacher of grade V SD. The results showed that the well-designed media used in the learning activities as evidenced by the average validation value is in the valid category, the average of practicality test from the student's responses is in very appropriate category, and the average from teacher responses is in the practical category. Keywords: development, learning media, interactive multimedia, character values.